Circular RNA network plays a potential antiviral role in the early stage of JEV infection in mouse brain - Chen, Mengli; Kang, Lei; Zhang, Tong; Zheng, Jiayang; Chen, Dishi; Shao, Donghua; Li, Zongjie; Li, Beibei; Wei, Jianchao; Qiu, Yafeng; Feng, Xiuli; Ma, Zhiyong; et al. (Frontiers in Microbiology, 2024)
Japanese encephalitis is one of the most important insect-borne infectious disease with public health concern. The virus can break the blood-brain barrier and cause death or long-term sequela in infected humans or animals. Viral encephalitis is an important clinical feature of JEV infection. In recent studies, CircRNAs and related ceRNAs data illustrated the regulative role in many aspects of biological process and disease duration. It is believed that CircRNA regulates JEV infection in a ceRNA-dependent mechanism. In this study, brain tissues of experimental mice were sequenced and analysised. 61 differentially expressed circRNAs, 172 differentially expressed miRNAs and 706 differentially expressed mRNAs were identified by RNA-Sequencing and statistical analysis. CX3CR1 was determined as a key host factor impact JEV infection by microRNA interference measurement. CX3CR1 interaction network indicated circStrbp/miR709/CX3CR1 as a functional regulation axis. Further sequencing in BV2 cell shown CX3CR1 is a special target of miR-709 only during JEV infection. In summary, our study presented a new ceRNA pathway that impact JEV infection in vivo and in vitro, which could be a therapeutic target to fight against JEV.